In general, the derivative of a single term Ax^(n) is A n x^(n-1) .
And the derivative of a sum of many terms is the sum of the derivatives
of the individual terms.
Using these two rules, the derivative (with respect to 'x') of the expression
in the question is . . .
<em> Y' = -21x² - 16x + 6</em>
Answer:
c
Step-by-step explanation:
.............,.......... confused with a and c
Where is the question to this or is this the answer
Answer:
The slope is
.
Step-by-step explanation:
The equation is conveniently in slope-intercept form.
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
m - slope
b - y-intercept
-2/3 is in m's spot, so it is the slope of the equation.
![y=\boxed{m}x+b\\\\y=\boxed{-\frac{2}{3}}x+5](https://tex.z-dn.net/?f=y%3D%5Cboxed%7Bm%7Dx%2Bb%5C%5C%5C%5Cy%3D%5Cboxed%7B-%5Cfrac%7B2%7D%7B3%7D%7Dx%2B5)
Hope this helps.